Management of Neglected Pediatric Monteggia Fracture-Dislocation: A Case Report with Literature Review - Sudhir Shankar Mane; Jayaram Reddy P.; Kyatham L. Jagadishwer Rao (Journal of Orthopedic and Spine Trauma)
Background: Missed or neglected Monteggia lesions are defined as the classical fracture-dislocation presenting at least four weeks after injury. This injury in children is often challenging to treat and requires complex methods to achieve optimal results.